2006
DOI: 10.1177/172460080602100302
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Treatment Prediction of Chemoresistance in Second-Line Chemotherapy of Ovarian Carcinoma: Value of Serological Tumor Marker Determination (Tetranectin, YKL-40, CASA, CA 125)

Abstract: Low serum levels of tetranectin, or high serum levels of CASA or YKL-40, are associated with increased risk of second-line chemoresistance in patients with ovarian cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 43 publications
(45 reference statements)
2
14
0
Order By: Relevance
“…In the present study plasma was available from a small subgroup of patients with borderline ovarian tumors and OCs, and in accordance with the studies mentioned above [23-26] we also found that elevated preoperative plasma concentrations of YKL-40 significantly predicted short survival in patients with OC. However, we did not find any correlation between plasma and tissue score YKL-40 in corresponding tissue and YKL-40 level in plasma samples in this subgroup of OC patients.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In the present study plasma was available from a small subgroup of patients with borderline ovarian tumors and OCs, and in accordance with the studies mentioned above [23-26] we also found that elevated preoperative plasma concentrations of YKL-40 significantly predicted short survival in patients with OC. However, we did not find any correlation between plasma and tissue score YKL-40 in corresponding tissue and YKL-40 level in plasma samples in this subgroup of OC patients.…”
Section: Discussionsupporting
confidence: 91%
“…There are no published studies on YKL-40 protein expression in OC tissue, and to our knowledge no publications exist on a close association between serum YKL-40, serum CA-125 and CA15-3 in patients with OC [23-26]. It has previously been shown that preoperative serum or plasma concentrations of YKL-40 are elevated in 65% of patients with FIGO stage I and II, and in 74% to 91% of patients with FIGO stage III and IV [23,24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gronlund et al reported that high serum levels of YKL-40 were associated with increased risk of second-line chemoresistance in patients with ovarian cancer [28]. However, Thöm et al found that the pretreatment serum YKL-40 level had no impact on response to chemotherapy in non-small cell lung cancer (NSCLC) [20].…”
Section: Discussionmentioning
confidence: 99%